Pembelajaran Matematika Menyenangkan pada Anak-Anak di Jemaat GMIT Logos Kilakawa - Narita Yuri A; Jeni M. Loban; Landerius Maro (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
Most children are very unenthusiastic about learning mathematics. This service is carried out so that the children of the GMIT Logos Kilakawa Congregation are motivated so that the children are more enthusiastic in learning mathematics so that they are no longer afraid of mathematics and they don't even experience difficulties. The methods used are tutoring and playing. The result of this activity is that the children are very enthusiastic and want to learn more about mathematics.